Does fluoxetine improve recovery after stroke?. (25th March 2019) - Cook, Rob; Thomas, Vaughan; Martin, Rosie
The study: FOCUS Trial Collaboration. Effects of fluoxetine on functional outcomes after acute stroke (FOCUS): a pragmatic, double-blind, randomised, controlled trial. Lancet 2019;393:256-74. The study was funded by the UK Stroke Association and the NIHR Health Technology Assessment Programme project number 13/04/30. To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000729/a-commonly-used-antidepressant-doesnt-improve-recovery-after-stroke